The International Criminal Police Organization and its Role in Iraq - Aziz, Peshraw Hamjan (Journal of Legal and Political Studies, 2017)
the development of technology, international trade, economic globalization and the weakness of the political border Led to the globalization of crimes, the emergence of international criminal organizations and the escape of criminals easily between states to get rid of the criminal justice, In contrast, The weakness of the local authorities Against this phenomenon led to that the states is thinking about developing, activating and internationalizing of the International criminal Police Organization (1956) (which International criminal Police committee (1923) previously) as a International mechanism to combat cross-border crimes, extradition between states, and States' adherence to it, until the number of its members arrived at (190) states, then the united nation recognized Interpol as an international organization 1971. this organization has NCBs in the Member States, which has its office in Baghdad, and a branch office in Kurdistan Region, in the context of this research, we study the character, the functions, the role of this organization, and the legal basis for the existence of its office in Iraq.
Keywords: technology; international trade; criminal justice; international criminal police organization